ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR PETANI DI KALIMANTAN BARAT - B01111018, HERIYANTO (Jurnal Pembangunan dan Pemerataan, 2015)
This thesis entitled "Analysis of the Factors that Influence the exchange Rate of Farmers in West Kalimantan" The purpose ofthis research is to analyze the factors that influence the exchange rate of farmers in West Kalimantan in 2005-2014 from January-December.   This research usesa model vector autoregressionand ordinary least square and the means of statistical analysis that is stationary test, cointergration test, vector error correction  model test,  impulse response function test, variance decompotiontest and statistical test, sample used in this research was 120 observation in west kalimantan province.   The result of this research shows that the inflation influences positive on exchange rate of farmers (stationary by the experiment adf level), while the cost of production, the loan interest rate and the rupiah exchange rate influences positive on exchange rate of farmers (stationary diferensiansi on the first phase ( 1st difference)). Trace statistic value and max-eigen statistic value are bigger than critical value which means that in the long term there is cointegration in that factors, while test t-statistik and the f-statistik all the variables significant on the exchange rate of farmers, the coefficients determination ( R2) as much as 0.978535 which means the size of the influence exerted by variable inflation, production costs, the loan interest rate and rupiah exchange rate on exchange rate of farmers in West Kalimantan is 98%, while the remaining is 2% which influences by another factor.   Keywords: exchange rate of farmers, inflation, cost production, loan interest rate and rupiah exchange rate